2014
DOI: 10.1038/mp.2013.194
|View full text |Cite
|
Sign up to set email alerts
|

APOE2 enhances neuroprotection against Alzheimer’s disease through multiple molecular mechanisms

Abstract: The common APOE2 gene variant is neuroprotective against Alzheimer's disease (AD) and reduces risk by nearly 50%. However, the mechanisms by which APOE2 confers neuroprotection are largely unknown. Here we showed that ApoE protein abundance in human postmortem cortex follows an isoform-dependent pattern (E2>E3>E4). We also identified a unique downstream transcriptional profile determined by microarray and characterized by downregulation of long-term potentiation (LTP) related transcripts and upregulation of ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
94
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(100 citation statements)
references
References 53 publications
4
94
0
1
Order By: Relevance
“…These increases are particularly pronounced in APOE*ε4 carriers 156 , findings comparable to those in transgenic APOE*ε4 mice 71 , which suggests that these increases represent activation of a BBB-degrading pathway involving cyclophilin A and MMP9. Activation of this cyclophilin A–MMP9 pathway has been confirmed by CSF analysis in non-symptomatic APOE*ε4 carriers, in whom it is associated with BBB breakdown 201 , and by analysis of cyclophilin A mRNA levels in brain tissue 202 . As the cyclophilin A inhibitor alisporivir has shown promise in a phase III clinical trial as an add-on treatment for hepatitis C 203 , these studies raise a possibility that these agents might also be useful in stabilizing the BBB in APOE*ε4 AD carriers.…”
Section: Postmortem Evidence Of Bbb Disruptionmentioning
confidence: 84%
“…These increases are particularly pronounced in APOE*ε4 carriers 156 , findings comparable to those in transgenic APOE*ε4 mice 71 , which suggests that these increases represent activation of a BBB-degrading pathway involving cyclophilin A and MMP9. Activation of this cyclophilin A–MMP9 pathway has been confirmed by CSF analysis in non-symptomatic APOE*ε4 carriers, in whom it is associated with BBB breakdown 201 , and by analysis of cyclophilin A mRNA levels in brain tissue 202 . As the cyclophilin A inhibitor alisporivir has shown promise in a phase III clinical trial as an add-on treatment for hepatitis C 203 , these studies raise a possibility that these agents might also be useful in stabilizing the BBB in APOE*ε4 AD carriers.…”
Section: Postmortem Evidence Of Bbb Disruptionmentioning
confidence: 84%
“…In addition, a recent study on the basis of postmortem brain tissue analysis reported that CypA mRNA levels are reduced in APOE2 carriers further supporting the role of CypA in regulating neurovascular function. 39 On a technical note, an earlier study reported decreased absolute values for the capillary length density in the cortex in control subjects. 40 A number of factors might have contributed to discrepant results with the present study such as to name a few, use of a different molecular marker to determine capillary length, i.e., endothelial-specific lectin versus the basement membrane protein collagen IV, different thickness of tissue sections, i.e., 10 mm versus 50 mm that can potentially affect differential penetration of primary antibodies into the respective tissue specimens, differences in the Brodman areas studied, different PMI, i.e., 3 to 10 hours versus 14 to 24 hours, and a different quantification method, i.e., 15 images per specimen derived from five fields per section in three adjacent sections 100 mm apart per specimen versus stereological measurements, in the present versus earlier study, 40 respectively.…”
Section: Discussionmentioning
confidence: 98%
“…Compared to apoE3, the presence of one and, particularly, two apoE4 alleles increases the risk of AD in humans by more than threefold and tenfold, respectively (Roses 1996 ), making apoE4 the major genetic risk factor for AD (Corder et al 1993 ;Saunders et al 1993 ;Strittmatter et al 1993 ). In contrast, apoE2 is more protective against AD as compared to apoE3 and apoE4 (Rebeck et al 2002 ;Conejero-Goldberg et al 2014 ).…”
Section: Apoe Structure Function and Isoform-specifi C Effectsmentioning
confidence: 94%